Attachment of β-Cyclodextrins on Cotton and Influence of β-Cyclodextrin on Ester Formation with BTCA on Cotton. Issue 3 (May 2014) - Bhaskara, Usha Rashmi; Tourrette, Audrey; Jocic, Dragan; Warmoeskerken, M. M. C. G.
Cotton was treated with β-cyclodextrin (BCD) and two derivatives of β-cyclodextrin (2-hydroxypropyl-β-cyclodextrin and monochlorotriazinyl-β-cyclodextrin) to assess the optimal type for fixation with cotton. The experimental results showed that treatment of cotton with BCD using the crosslinker BTCA resulted in higher fixation than the treatments with the other two derivatives. The concentration of BTCA used did not significantly influence the amount of fixation of BCD on cotton. FTIR-ATR spectroscopic analysis showed that the amount of ester formed on the fabric was influenced by the addition of BCD on cotton with BTCA in comparison to crosslinking of only BTCA with cotton. The laundering tests showed relatively poor washfastness of the β-cyclodextrins on the fabrics.